Subsidy reform and sustainable development economic, environmental and social aspects. (OECD sustainable development studies., 2006)
Subsidies are pervasive in OECD countries and are among the most powerful public policy instruments. But they often introduce unintended consequences, such as budget deficits, pollution, unemployment and trade distortions. This report contains the proceedings of an OECD workshop on subsidy reform held in October 2005 under the auspices of the OECD program on sustainable development. It provides an overview of approaches for assessing subsidies and associated taxes, and looks at country experiences in reforming subsidies in the agriculture, fisheries, industry, and transport sectors.--Publisher description.